Menumbuhkan Kecerdasan Ekologis Siswa melalui Kearifan Lokal Masyarakat Kampung Naga dalam Pembelajaran Sejarah - Febriantie, Sekar Ayu (Lembaga Yasin AlSys, 2023)
Humans are God's most perfect creatures on earth, this is because humans are endowed with reason and thought. Humans should be able to use this mind to be able to adapt in carrying out their lives. In adapting, of course, humans do not escape the process of interaction with their environment. It is undeniable that currently the interactions that occur between humans and their environment can have negative and positive impacts. One of the negative impacts caused is the excessive exploitation of the environment in order to meet human needs which of course are endless. Developing students' ecological intelligence through the concept of ecopedagogy in history learning is very important in order to create students who have a critical view of the importance of the concept of sustainable development. One of the things that can be done by the teacher is to relate the material being taught by providing understanding to students so that they can live by instilling environmentally friendly principles. An example is through the process of internalizing ecosystem awareness which is done naturally, namely by developing attitudes, lifestyles, and traditions that have a positive impact on the balance of the ecosystem. This tradition is also known as an application of local wisdom. One of them is through local wisdom in Kampung Naga.